La survivance du passé : een onderzoek in vier episoden naar het werkelijkheidskarakter van de tijd. - s.n. (Amsterdam : Galerie Ferdinand van Dieten - d'Eendt, 1998)
The project Survivance du Passé consisted of a series of four exhibitions and two symposia. La survivance du passé, Galerie Ferdinand van Dieten - d'Eendt, Amsterdam, 13.02.1998 - 22.03.1998
In the post-modernist debate, thinking about time achieved a specific position. Do we live by now in a post-historic time ? Has with this the balance moved from the objective time of the art history and the belief in a continuous progress, to a more subjective experience of the ephemeral ? Or has the present cultural logic that is fixated on space, translated the dimension of time in a process of difference and repetition ?
Obviously, a work of art never coincides in full with one of these ways to consider the reality of time. It will be examined which of these different dimensions are more or less typical for the way the presented art works relate to time.
The premise of departure is made up with the thought that it is an essential aspect of art to provide us with an intuition of the nature of temporal reality. Achieving such an intuition may occur from various perspectives: systematising and dramatising the specific ephemeral; opposing the objective quality of time with the subjectivity of perception; accentuating the dialectics of difference and repetition.
The project La Survivance du passé intends to examine this question in a laboratory set-up, whereby the action of space and time will be variable.
The project attempts to promote by means of a sequence of arrangement experiments, the theoretic reflection (especially in the Netherlands) about the position and the conditions of existence of the image in the present culture.
To accentuate the dialectics of difference and repetition more specifically, the presentation of La survivance du passé will be realised in four episodes for ever-changing international art contexts, where works and/or artists could be substituted. The four forms of presentation are: gallery presentation (Amsterdam, March 1998), art fair presentation (Basel 1998), congress presentation (International Association of Aesthetics Congress, Ljubjana, September 1998), art space (Berlin, December 1998). Furthermore, parallel and extramural activities, such as a symposium and a publication (Spring 1998) will be staged.
Keywords: Visch, Henk; Langenberg, Sjaak; Kinoshita, Suchan; de Gruyter, Voebe; van Muiswinkel, Wineke